Faktor Risiko Kejadian Infeksi Daerah Operasi pada Bedah Digestif di Rumah Sakit Swasta - Nirbita, Alam; Rosa, Elsye Maria; Listiowati, Ekorini (Universitas Ahmad Dahlan, 2017)
Background: The incidence of IDOs in hospitals in Indonesia varies between 2-18% of all surgical procedures. No research has been done on the effects of IDO risk factors with IDO incidence in gastrophic surgery at this hospital. This study aims to determine the effect of IDO risk factors consisting of nutritional status, type of surgery, the nature of surgery, and durante surgery against the incidence of IDO in surgical patients digestif. Method: This research is an observational quantitative study. The data taken are primary (observasional) and secondary (medical record) using cross sectional method. The data were then analyzed by Chi-square bivariate and multivariate test. Result: Based on Chi-square bivariate test, the variables: operation type (p=0.000), durante surgery (p=0.000), and operational properties (p=0.029) have significant relationship while nutritional status (p=0.055) which is significant against IDO events. Conclusion: The result of multivariate test showed that the variables: nutritional status (p=0.032), type of operation (p=0.006), and durante (p=0.008) had significant influence with the type of operation is the most influential on IDO event.